Body and origami: a study on innovation of folds in contemporary art (Palíndromo, 2015)
This article analyzes the contem- porary art in union with the creative techniques of body and origami, cre- ating connections between different body arts and the technology applied to them. In a first moment, we analyze the contemporary scene, the new technol- ogies and the paths of today’s society. In a second moment, it is considered the body’s behavior and origami insert- ed within this new context. Finally, some projects are analyzed using body per- formance and Japanese folding as main foundation.
Keywords: body; origami; art; folds; contemporary